UPAYA MENGATASI KESULITAN SISWA DALAM MEMBEDAKAN BUNYI VOKAL DALAM BAHASA INGGRIS MELALUI FLASH CARD - Rahmii; Siti Rusdayanti; Rezki Ramdani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
ABSTRACT This research concentrates on the problems students face in differentiating vowel sounds in English, which often becomes an obstacle in language learning. The purpose of this study was to determine how effective flash cards are as a way to help students understand and differentiate vowel sounds. This research uses a quantitative approach and uses an experimental design. This study involved fifth grade students at SDN Labuang Baji 1. Students were divided into two groups: the experimental group used flash cards and the control group used conventional learning. Data collection was carried out through pre-tests and post-tests to measure differences in students' ability to differentiate vowel sounds before and after intervention. The results of the study showed a significant increase in the experimental group. The average final test score of the group using flash cards increased by 30% compared to the control group. This indicates that the use of flash cards is effective in helping students understand and differentiate vowel sounds in English. This research concludes that the flash card method can be used as an alternative in teaching English to overcome the difficulties faced by students, as well as encourage teachers to implement innovative learning strategies.